Comparative insights into soybean and other oilseed crops’ defense mechanisms against Sclerotinia sclerotiorum - Talmo, Nick; Ranjan, Ashish (Frontiers in Plant Science, 2025)
Sclerotinia sclerotiorum is a devastating fungal pathogen capable of causing substantial yield loss on a wide range of agronomically important crops worldwide. S. sclerotiorum’s impressive virulence across its broad host range is primarily due to the abundance of pathogenic strategies at its disposal. These pathogenic strategies include the use of organic acids, hydrolytic enzymes, and various effector molecules that work in concert during host attack. While plants have evolved sophisticated defense mechanisms, complete resistance to S. sclerotiorum remains elusive among the more than 400 known plant hosts. Among these hosts, soybean, canola, and sunflower are the most important oilseed crops severely affected by S. sclerotiorum infection, which can result in 94% crop loss in extreme cases. Current management strategies rely on chemical fungicides, crop rotations, and partially resistant varieties, albeit with varying levels of success. Despite extensive research on individual host-pathogen interactions, there is a notable gap in comparative studies exploring defense mechanisms across plant families. This review seeks to address this gap by providing an overview of known defense strategies against Sclerotinia stem rot (SSR) in soybean and canola, as well as head rot (SHR), mid-stalk rot (MSR), and basal stalk rot (BSR) in sunflower. By identifying commonalities and differences among distantly related hosts, this comparative analysis aims to deepen our understanding of key plant defense strategies against S. sclerotiorum, thereby highlighting areas requiring future research.